Hereditary haemochromatosis presenting to rheumatology clinic as inflammatory arthritis. Issue 1 (17th January 2022) - Hum, Ryan Malcolm; Ho, Pauline
Abstract : Hereditary haemochromatosis (HH) is the most commonly identified genetic disorder in Caucasians. HH has a wide variety of clinical manifestations. As such, the presenting complaint in new diagnoses of HH can be non-specific such as fatigue; however, joint symptoms such as arthralgia are also common. These joint symptoms closely mimic the features of other musculoskeletal diseases such as rheumatoid arthritis (RA). Early diagnosis of HH is key to prevent long-term irreversible complications such as liver damage, diabetes and degenerative joint disease. We present a case of HH which was initially suspected to be early RA, with ultrasound findings of active synovitis. High clinical suspicion, a raised serum ferritin followed by genetic testing for C282Y mutation confirmed the diagnosis of HH. The synovitis responded to corticosteroids and was suspected to be due to pseudogout a known complication of HH. Early diagnosis and treatment resulted in a favourable outcome.